Bio‐inspired optical structures for enhancing luminescence - Zemin Zhang; Florian Vogelbacher; Yanlin Song; Yang Tian; Mingzhu Li (Exploration, 2023)
Abstract Luminescence is an essential signal for many plants, insects, and marine organisms to attract the opposite sex, avoid predators, and so on. Most luminescent living organisms have ingenious optical structures which can help them get high luminescent performances. These remarkable and efficient structures have been formed by natural selection from long‐time evolution. Researchers keenly observed the enhanced luminescence phenomena and studied how these phenomena happen in order to learn the characteristics of bio‐photonics. In this review, we summarize the optical structures for enhancing luminescence and their applications. The structures are classified according to their different functions. We focus on how researchers use these biological inspirations to enhance different luminescence processes, such as chemiluminescence (CL), photoluminescence (PL), and electroluminescence (EL). It lays a foundation for further research on the applications of luminescence enhancement. Furthermore, we give examples of luminescence enhancement by bio‐inspired structures in information encryption, biochemical detection, and light sources. These examples show that it is possible to use bio‐inspired optical structures to solve complex problems in optical applications. Our work will provide guidance for research on biomimetic optics, micro‐ and nano‐optical structures, and enhanced luminescence.